Alat Pengisian Bensin Pada Penjual Besin Eceran Menggunakan Sistem Flow Sensor - Subandi; Prastiono Eko Pambudi; Gatot Santoso; Slamet Hani; Danang Ari Setyo Wibowo (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2020)
At this time, retail gasoline sellers are often found on the side of the road, both on the side of the highway to the rural road. Indeed, they are very helpful for motorists when the vehicle they are riding in occurs a problem, namely running out of fuel. However, when buying from a retail gasoline seller, you are often worried about what the gasoline sellers are selling, namely whether the amount of gasoline they sell is in accordance with the actual quantity. To reduce this worry, a retail petrol filling device was made according to the dosage which functions to reduce the worry by using a flow sensor system as a detection of the correct dose. Filling gasoline using this flow sensor includes a minimum series of the ATMega8 microcontroller system as a control unit, a power supply circuit as input, a motor driver circuit, and a pump motor as output. This cool petrol filling tool has optimal flow sensor accuracy, because from 5 trials for the volume of 1 liter of gasoline, the average error obtained is only 1.6 seconds.